Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/dmrr.2832
|View full text |Cite
|
Sign up to set email alerts
|

Skin autofluorescence and peripheral neuropathy four years later in type 1 diabetes

Abstract: Objective Advanced glycation end products (AGEs) are involved in diabetes complications. We aimed to investigate whether the accumulation of AGEs measured by skin autofluorescence (sAF) was associated with signs of diabetic peripheral neuropathy and to sensitivity, pain, motor and autonomic function 4 years later in patients with type 1 diabetes.Methods At baseline, 188 patients (age 51 years, diabetes duration 22 years) underwent skin autofluorescence measurement using the AGE Reader. Four years later, signs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…[30][31][32] In accordance with the literature, we also found that both the monofilament and neurothesiometer tests reported a higher risk of neuropathy in those groups with high LFRs. 29 In this study, we also found significant relationships between the LFR and both HbA 1c levels and the duration of diabetes, which is consistent with the literature. 33,34 On the other hand, we did not find any relation with age and lens fluorescence.…”
Section: Assessment Of Diabetic Peripheral Neuropathysupporting
confidence: 92%
“…[30][31][32] In accordance with the literature, we also found that both the monofilament and neurothesiometer tests reported a higher risk of neuropathy in those groups with high LFRs. 29 In this study, we also found significant relationships between the LFR and both HbA 1c levels and the duration of diabetes, which is consistent with the literature. 33,34 On the other hand, we did not find any relation with age and lens fluorescence.…”
Section: Assessment Of Diabetic Peripheral Neuropathysupporting
confidence: 92%
“…In 240 patients with type 1 diabetes, we measured sAF during year 2009 . We have recently reported that these sAF were associated to diabetic peripheral neuropathy and that they predicted later estimated glomerular filtration rates and cardiovascular events . One hundred and fifty‐four patients had a second sAF measurement 4 years later.…”
Section: Introductionmentioning
confidence: 99%
“…In situations of metabolic and oxidative stress, however, accelerated AGE accumulation rates have been described, such as in individuals with cardiovascular disease (CVD) [ 1 , 2 ] and diabetes mellitus (DM) [ 3 , 4 ]. The fairly quick (seconds) and non-invasive assessment of skin autofluorescence (SAF) has been demonstrated to serve as a surrogate marker of tissue accumulation of AGEs [ 5 , 6 ] and recent efforts have been undertaken to develop stratification tools for the clinical assessment of a patient's risk for cardiovascular disease (CVD) [ 7 9 ] and diabetic complications [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%